PELATIHAN PEMASARAN DAN PENGELOLAAN KEUANGAN USAHA SABLON PADA MASA PANDEMI COVID-19 DI KEBONSARI KABUPATEN JEMBER - Galih Wicaksono; Krisnamurti Krisnamurti; Tree Setiawan Pamungkas (Batara Wisnu : Indonesian Journal of Community Services, 2022)
This Community Service Activity (PKM) in the form of the Partnership Service Program (PPK) was carried out on a screen printing business affected by the Covid-19 Pandemic in Kebonsari, Jember Regency. The business has problems in the fields of marketing and financial management, so it requires intervention from the campus world in the form of KDP activities. The purpose of this activity is to assist screen printing business actors in sustaining their business, namely in the aspects of marketing and financial management. To overcome these problems, the activities carried out are in the form of marketing training, financial and tax management, as well as activity evaluation. The result of this activity is that the screen printing business partner has significant knowledge and skills related to aspects of marketing and financial management, so it is hoped that the sustainability of their business will improve during the current pandemic